2014
DOI: 10.1245/s10434-014-3731-5
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life is Modestly Improved in Older Patients with Mild Primary Hyperparathyroidism Postoperatively: Results of a Prospective Multicenter Study

Abstract: This study showed, in patients with mild pHPT, an improvement of QoL 1 year after parathyroidectomy. Patients <70 years and with calcemia ≥10.4 mg/dL had a more significant improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 20 publications
2
12
0
1
Order By: Relevance
“…(27) reported that reduced baseline HRQoL improved with surgery in randomized trials of 50 and 53 PHPT patients not fulfilling surgical criteria, as assessed by the SF-36. Other studies on mild PHPT reported similar findings (28, 29). Of note, in the present study, total 15D scores significantly improved at 6 and 12 months after surgery compared to baseline in the patients, but were still slightly lower than those observed in controls (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…(27) reported that reduced baseline HRQoL improved with surgery in randomized trials of 50 and 53 PHPT patients not fulfilling surgical criteria, as assessed by the SF-36. Other studies on mild PHPT reported similar findings (28, 29). Of note, in the present study, total 15D scores significantly improved at 6 and 12 months after surgery compared to baseline in the patients, but were still slightly lower than those observed in controls (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Numerous observational studies have evaluated the effect of PTX in PHPT using the SF‐36 survey as well as other non‐disease‐specific questionnaires, suggesting improvement in HRQoL . An observational study by Rolighed et al HRQoL, assessed by SF‐36, were reduced in all 8 domains compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…However, these nonspecific symptoms are difficult to quantify, and it is unclear to what extent these symptoms are related to PHPT and whether parathyroidectomy (PTX) relieves the symptoms. Most studies, so far, have evaluated health‐related quality of life (HRQoL) in PHPT using non‐disease‐specific questionnaire such as the Short Form‐36 (SF‐36) general health survey . Four randomized clinical trials (RCTs) assessed HRQoL in asymptomatic PHPT patients, including effect of parathyroidectomy (PTX).…”
Section: Introductionmentioning
confidence: 99%
“…In two previous studies, Blanchard and colleagues evaluated non‐specific symptoms and their impact on QoL in patients with Hc‐m‐PHPT who were later treated by parathyroidectomy; they concluded that surgery does improve QoL and non‐specific symptoms in this group, with better results among younger patients. These findings form the basis of the present study of whether the same non‐specific symptoms are observed in NcPHPT, how these affect QoL, and whether parathyroidectomy could help alleviate some of these symptoms or improve the QoL of patients with normocalcaemia.…”
Section: Introductionmentioning
confidence: 99%